Manajemen Risiko dan Media Exposure sebagai Pemoderasi Pengaruh Corporate Social Responsibility terhadap Nilai Perusahaan High Profile di Indonesia - Rosida Majid (2021)
CSR information can give positive signal to its readers, especially investors in making investment decisions, thus affecting the value of the company. The application of appropriate risk management in the company's operational activities can minimize the possibility of failure of the company's activities including the company's CSR activities and provide added value for the company. The interest of high-profile companies to disclose their CSR activities is greater than that of low-profile companies. Due to their high sensitivity to the company's external interests, high profile companies are not spared from the media. This study aims to obtain empirical evidence on the influence of CSR on the firm value of high profile companies in 2016-2018 along with risk management and media exposure as moderators of this influence. The research method used is a quantitative method with partial regression analysis techniques and moderation obtained from secondary data of 69 research samples. The results of the analysis state that there is a significant positive effect of CSR on the firm value of high profile companies. However, risk management and media exposure cannot moderate the effect of CSR on the firm value of high profile companies.